Quantitative analysis of cellular lipids by nano-electrospray ionization mass spectrometry - Özbalcı, Çağakan; Sachsenheimer, Timo; Brügger, Britta (Membrane Biogenesis, 2013)
Lipid analysis performed by nano-electrospray ionization mass spectrometry is a highly sensitive method for quantification of lipids including all lipid species of a given lipid class. Various instrumental setups are used for quantitative lipid analysis, including different modes of ionization, separation, and detection. Here we describe a work-flow for the rapid and quantitative analysis of lipid species from cellular membranes by direct infusion of lipid extracts to a nano-electrospray ionization triple quadrupole/linear ion trap mass spectrometer.